PENGARUH LEVERAGE,FINANCIAL DISTRESS DAN GROWTH OPTIONS TERHADAP AKTIVITAS HEDGING PADA PERUSAHAAN NON-KEUANGAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Hafis Nuzul; Maya Febrianty Lautania (Accounting Departement Economics and Business Faculty Syiah Kuala University, 2015)
AbstractThis research aims to examine the influence of leverage, financial distress, and growth options on probability of the corporations to execute hedging activities using derivative instruments.The population of this research consist of non financial companies which are listed on IDX (Indonesia Stock Exchange) from 2012-2014.The samples of 210 companies were selected using slovin formula and simple random sampling technique. Hypothesis were tested utilizing logistic regression analysis.The results of this research show that leverage, financial distress, and growth options simultaneously influence the hedging activities by using derivative instruments. Partially leverage influence the hedging activities by using derivative instruments mean while financial distress and growth options do not influence hedging activities by using derivative instruments. Keywords: derivative instruments, financial distress, growth option, Hedging, leverage